36.9k views
1 vote
) () = 2 − 6 + 13 Translate f(x) 7 units to the left and down 5 units. Write your new function in vertex form

User Jiri Mares
by
5.3k points

1 Answer

6 votes

Answer:


y= (x -4)^2 - 1


Vertex = (4,-1)

Explanation:

Given


f(x) = x^2 + 6x+13

Required

7 units left and 5 units down

First, we have: [7 units left]

The rule is:


(x,y) \to (x-7,y)

So, we have:


f(x) = (x - 7)^2 + 6(x -7)+13

Next, we have: [5 units down]

The rule is:


(x,y) \to (x,y-5)

So, we have:


f'(x) = (x - 7)^2 + 6(x -7)+13 - 5


f'(x) = (x - 7)^2 + 6(x -7)+8

Rewrite as:


y = (x - 7)^2 + 6(x -7)+8

Expand


y = x^2 - 14x + 49 + 6x -42+8

Collect like terms


y = x^2 - 14x + 6x -42+8+ 49


y = x^2 -8x +15

To write in vertex form, we have

Subtract 15 from both sides


y -15= x^2 -8x

Divide (-8) by 2; Add the square to both sides


y -15+ (-8/2)^2= x^2 -8x + (-8/2)^2


y -15+ 16= x^2 -8x + 16


y +1= x^2 -8x + 16

Expand


y +1= x^2 -4x - 4x + 16

Factorize


y +1= x(x -4) -4(x - 4)

Factor out x - 4


y +1= (x -4)(x - 4)

Rewrite as:


y +1= (x -4)^2

Make y the subject


y= (x -4)^2 - 1

The vertex is:


Vertex = (4,-1)

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.